Justiça restaurativa: um novo paradigma para a superação da vingança? - Maia, Diego Dall’ Agnol (2019)
The present research has as objective to investigate if restorative justice succeeds in overcoming revenge, trying to understand if, effectively, it is possible to deinterlace the revenge of justice. Because it is a contemporary challenge, the creation of new models to respond to the conflicts of an increasingly complex society occupies a prominent place, especially considering the difficulties faced by justice systems and the dissatisfaction of individuals seeking a resolution of conflicts. In addition, the need for separation from revenge and justice is also a source of concern, which raises the question whether the desire for revenge can be satisfied by law, when emotions influence the process of norm-making and decisions. Foreign works were analyzed, mostly produced from studies conducted in the United States, Ireland, Italy, France and England, as well as suggestions and criticisms, aiming at a better understanding of the question posed for analysis. In fact, restorative justice did not emerge in Brazil, consequently all theoretical influence and practical development is the result of research that is carried out in the United States and Europe. The method used in this dissertation was the exegetical one with the search of information in books, jurisprudence, laws, internet, with the adoption of a critical position on the data and information obtained